The Salience of Social Contextual Factors in Appraisals of Police Interactions with Citizens: A Randomized Factorial Experiment - Braga, Anthony A.; Winship, Christopher; Tyler, Tom R.; Fagan, Jeffrey; Meares, Tracey L. (Journal of quantitative criminology, 2014)
Objectives Prior research indicates that public assessments of the manner in which the police exercise their authority are a key antecedent of judgments about the legitimacy of the police. In this study, the importance of context in influencing people's assessment of police wrongdoing is examined. Methods A randomized factorial experiment was used to test how respondents perceive and evaluate police-citizens interactions along a range of types of situations and encounters. 1,361 subjects were surveyed on factors hypothesized to be salient influences on how citizens perceive and evaluate citizen interactions with police. Subjects viewed videos of actual police-citizen encounters and were asked for their evaluations of these observed encounters. Contextual primes were used to focus subjects on particular aspects of the context within which the encounter occurs. Results Structural equation models revealed that social contextual framing factors, such as the climate of police-community relations and the legality of the stop that led to the encounter, influence citizen appraisals of police behavior with effects comparable in size to and even larger than demographic variables such as education, race, and income. Conclusions These results suggest that the understandings and perceptions that people bring to a situation are important determinants of their assessment of police fairness. The police can positively influence citizen interpretations of police actions by striving to create a climate of positive police-community relationships in cities.